Sprinkler irrigation in the production of safe rice by soils heavily polluted by arsenic and cadmium. (August 2021) - Spanu, Antonino; Langasco, Ilaria; Serra, Marco; Deroma, Mario Antonello; Spano, Nadia; Barracu, Francesco; Pilo, Maria I.; Sanna, Gavino
Abstract: Among the factors affecting the bioaccumulation of As and Cd in rice, a key role is played by the irrigation methods. The sprinkler irrigation (SP), optimized for rice in Sardinia, Italy, applied to several rice genotypes over many years has produced no differences in yields in comparison to what observed using the traditional continuous flooding irrigation method (CF). Because all the previous SP trials have been performed just on one, unpolluted soil, the principal aim of this study is to ascertain the effectiveness of SP to simultaneously minimize the bioaccumulation of As and Cd in rice grain even in soils severely polluted by As and/or Cd. Hence, a Carnise rice genotype was cultivated in an open field in: i) an unpolluted soil; ii) a soil polluted with 55 mg kg −1 of As; iii) a soil polluted with 40 mg kg −1 of Cd; iv) a soil polluted with 50 mg kg −1 of As and 50 mg kg −1 of Cd. In the worst condition of pollution, the amounts of total As and Cd measured in the kernels using a fully validated ICP-MS method is 90 ± 10 μg kg −1 and 50 ± 20 μg kg −1, respectively, i.e. less than 50% and the 25% of the maximum concentration set for these elements in rice by the European Community (200 μg kg −1 for the inorganic As and the total amount of Cd, respectively). SP might represent a simple and valuable tool able to produce safe rice also from soils where the traditional irrigation might produce inedible rice only. Graphical abstract: Image 1 Highlights: Sprinkler irrigation (SP) of rice reduce water needs and amounts of toxic elements. Carnise rice strongly accumulates As in grains under flooded paddy conditions. SP decreases As & Cd in grains in unpolluted soil but in polluted soil is unknown. Carnise kernels irrigated with SP by soils with 50 mg kg −1 of As and Cd are safe.